On the Teaching Contents of Writing a Formal Academic Summary - Stanevičienė, Benedikta Zinaida (Acta Paedagogica Vilnensia, 2007)
The article is intended to render assistance to university lecturers in teaching their students to write a formal academic summary of their speciality texts. Summary writing is one of the requirements of the curriculum in higher schools. However, according to our findings only a small number of students can successfully cope with this task. As far as we know there does not exist a study on teaching contents for writing a formal academic summary. In the article an attempt has been made to determine the contents of teaching this kind of writing. It should include two components, those of linguistic and psychological nature. Attention is drawn to importance of teaching to become aware of the text structure. The component of the linguistic nature should take into account the structure of both the primary and the student-generated texts. The other linguistic means necessary to write a formal academic summary such as vocabulary and grammar have not been discussed in this article. It is emphasized that only the 1st and the 2nd level information of the primary text which constitute the core of the text information should be included in a formal academic summary. The psychological component of the teaching contents to write a formal academic summary should consist of the abilities to be developed in writing the summary such as a mature reading, paraphrasing, note taking, condensing (distilling) the information of the primary text. A methodological and psychological mechanism of reducing the primary text to its summary and further to its annotation has been worked out. It visually shows the teaching contents of writing a formal academic summary. Lecturers’ and students’ awareness of the presented teaching contents should improve teaching to write a formal academic summary as well as to more precisely assess it to meet the requirements set forth in the examinations for higher schools.